Photophysical studies of Zinc phthalocyanine-silica nanoparticles conjugates - Fashina, Adedayo (Rhodes University, Faculty of Science, Department of Chemistry, 2015)
This thesis reports on the synthesis and characterization of both symmetrical and asymmetrical Zinc phthalocyanine complexes. The complexes contained groups such as carboxylic, amino and alkyne for covalent grafting to the surface of silica nanoparticles. The use of symmetrical and asymmetrical complexes was geared towards comparing the non-specific binding of the symmetrical complexes to the specific binding observed in the asymmetrical complexes. The complexes were also doped within the silica matrix and compared to the surface grafted conjugates. The complexes and the conjugates were well characterized with a variety of techniques. The fluorescence lifetimes of the phthalocyanine complexes containing either terminal carboxylic groups or an alkyne group showed a mono-exponential decay while the amino containing phthalocyanine complexes gave a bi-exponential decay. A similar trend was observed for their respective conjugates. Some of the conjugates of the asymmetrical complexes showed a decrease in fluorescence lifetimes and a corresponding decrease in fluorescence quantum yields. The fluorescence quantum yields for all the symmetrical complexes studied showed either an improvement or retained the luminescence of the grafted phthalocyanine complex. Most of the conjugates showed a faster intersystem crossing time in comparison to the complexes alone. The grafted or doped conjugates containing symmetrical phthalocyanine complexes with carboxyl groups showed improvements both in fluorescence and triplet quantum yields. All the conjugates except two showed an increase in triplet lifetimes when compared to their respective phthalocyanine complexes. Optical nonlinearities of nine of the phthalocyanine complexes were studied and all the complexes showed characteristic reverse saturable absorption behavior. Complex 10 showed the most promising optical limiting behavior. The aggregation and dissolution studies of the conjugates were also carried out in a simulated biological medium and the silicon level detected was noticed to have increased with incubation time.
Keywords: Nanoparticles; Phthalocyanines; Zinc; Silica; Photochemistry; Adsorption